Hail occurrence related to a mesoscale convective system that reached Rio Grande do Sul in august 2006 - Campos, Cláudia Rejane Jacondino de; Maria, Diogo Monteiro (Anuário do Instituto de Geociências, 2014)
This work analyzed thermodynamic and synoptic environmental characteristics associated with the occurrence of hail generated by a Mesoscale Convective System (MCS) that reached Rio Grande do Sul (RS) from 2006/08/14 to 2006/08/17, as well as morphological and radiative behavior of this MCS. These analyses allowed highlight the main atmospheric conditions which contributed for the occurrence of this event. The results showed that the atmospheric conditions observed in the region were extremely favorable to formation and development of the MCS that began in 2006/08/14, which favored the hail occurrence in 2006/08/15 in Victor Graeff and extreme precipitation in Northern RS in 2006/08/16.